School and territory: some feedback from the Self Evaluation Report - Rosanna Tammaro; Marika Calenda; Ciro Clemente De Falco; Concetta Ferrantino (Formare, 2017)
What is the relationship with the territory of high schools in the province of Salerno? Are there differences in the integration’s levels with the territory on the basis of different territorial spheres? To what extent do schools feel able to involve families in the formative project? Do the socio-economic characteristics of the area affect the action of the school? Which differences can we observe at national and regional level? This article aims to provide some answers to these questions through a descriptive analysis of integration with the territory of high schools in the province of Salerno, starting with the topic of quality in school management and self-evaluation like an agent for improvement. Specifically, a documentary analysis is carried out on the schools Self-assessment reports, analyzing contents of the answers provided by the compiler’s self-declaration.